2021
DOI: 10.1016/j.jpeds.2021.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight as an Early-Life Risk Factor for Adult Stroke Among Men

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…An inverse and independent of body mass index (BMI) relationship between low birth weight and stroke among adult men has recently been described. As such low birth weight should be considered in stroke risk assessment 24 …”
Section: Early Oxidative Stress and Maternal Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…An inverse and independent of body mass index (BMI) relationship between low birth weight and stroke among adult men has recently been described. As such low birth weight should be considered in stroke risk assessment 24 …”
Section: Early Oxidative Stress and Maternal Healthmentioning
confidence: 99%
“…As such low birth weight should be considered in stroke risk assessment. 24 Fetal exposure to high cholesterol levels, diabetes and obesity in the mother is associated with an increased risk for and progression of atherosclerosis. Infants born to mothers affected by hypercholesterolaemia during pregnancy display atherosclerotic lesions of the abdominal aorta, which are not present in infants born to mothers with normal cholesterol levels.…”
Section: Early Oxidative Stress and Maternal Healthmentioning
confidence: 99%
“…A recently published birth cohort study indicated a correlation between birth weight and brain volume in the elderly above 70 years of age ( 6 ). Lilja et al ( 7 ) found that an inverse association between birth weight and the risk of adult stroke, IS, and ICH independent of young adult BMI, suggest that low birth weight should be included in assessments of stroke risk in adults. The above research suggests that birth weight, as a common body measurement index, has great significance, but it is often ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Increased salt intake [9][10][11] exposure to environmental factors, family history studies [12] ecological correlation between low birth weight and risk of later stroke have all contributed to the stroke menace. [13] Others such as genetic factors can act at several levels, they contribute to conventional risk factors such as hypertension ,diabetes or increased homocysteine concentrations [14,15] and they could also affect latency to stroke ,infarct size or stroke outcome [16,17].There have been studies investigating potential risk genes for common multifactorial stroke such as Single -gene disorders ,Cerebral autosomal dominant arteriopathy with sub cortical infarcts and leuconcephalopathy(CADASIL), Fabry's disease, sickle -cell disease, connective tissue disorders most of these are associated with young stroke patients ,children and ischaemic stroke. Their impact on the population is large [18].…”
Section: Introductionmentioning
confidence: 99%